Trends in Stockholm Convention Persistent Organic Pollutants (POPs) in Arctic Air, Human media and Biota. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2014)
"This report summarises results of POPs (temporal) trend monitoring studies conducted under the auspices of the Arctic Monitoring and Assessment Programme (AMAP) that are relevant to the Stockholm Convention. Arctic Council Ministers have requested AMAP to present data products and collaborate with relevant Stockholm Convention groups in preparation for the Stockholm Convention’s Second Global Monitoring Plan (GMP) report due in 2015. This report is therefore prepared as an AMAP contribution to the Stockholm Convention (SC) GMP2 and the related effectiveness and sufficiency (Article 16) evaluation work to be performed by the SC-WEOG (Western Europe and Other) regional organization group. The report presents the results of statistical analyses of a large number of time-series data sets concerning POPs that are included under the Stockholm Convention in Arctic air (a GMP core media) and biota samples. A separate AMAP contribution covering Arctic human bio-monitoring data is also annexed to this report. The Arctic monitoring network is important to the work to evaluate the effectiveness and sufficiency of the Stockholm Convention since much of the Arctic is remote from the main industrial and agricultural areas where POPs are used and released to the environment. The Arctic region therefore includes both background monitoring sites, where contaminant levels can be expected to reflect long-range transport from global sources, and some sites where local sources have been identified and characterised. This report focuses mainly on temporal trend monitoring results at background locations, to allow the temporal development in POPs levels prior to and after their inclusion in the Stockholm Convention to be followed."